SEO Strategy Using Content Pillars and Long-Tail Keywords to Boost Organic Traffic - Nuri Cahyono; Kamarudin Kamarudin (Journal of Applied Informatics and Computing, 2026)
The issue of low content visibility in organic search results remains a major challenge in website management, particularly when content structures are disorganized and keyword selection is suboptimal. This study employs a descriptive quantitative approach through the implementation of content pillar and long-tail keyword strategies, complemented by structural connectivity analysis using a Content Relevance Matrix and Interlink Density (ILC) measurement. The research process includes topic mapping, the development of pillar and cluster articles, the evaluation of internal link density, and the analysis of organic performance using Google Search Console. The results indicate that clusters with the highest connectivity levels, such as C3 and C5, demonstrate a strong correlation with organic traffic performance, while the calculated ILC value of 53.57% reflects an efficient internal linking structure that enhances crawlability. Traffic evaluation further shows a significant outcome, with the highest value reaching 14,608 organic visits, aligning with the strengthened semantic relevance within the content structure.